Rethinking Autofiction from the Stage: A Reading of the Paradox of To Be or Not To Be in the Dramaturgy of Sergio Blanco - Luque, Gino (2023)
Despite the existence of performing practices that have explored the relationship between autobiography and fiction for a long time, theatrical autofiction has only recently begun to be studied. This is partly due to the particularities of theatrical communication that make traditional models of analysis, designed for narrative texts, unable to explain the dynamics of dramatic autofiction. This article proposes to rethink the theory of theatrical autofiction based on the inscription of the autofiction reading pacts in the conventions of theatrical reception. The discussion is based on the analysis of the dramaturgy of Sergio Blanco, whose work essentially explores the possibilities and limits of autofiction on stage.